Transitions to Motherhood in a Low-Fertility Country: Timing, Type, and Order of Life Course Events - Del Rey, Alberto; García-Gómez, Jesús; Orfao, Guillermo; Wu, Mengyao (Comparative population studies, 2025)
This study analyses the key transitions over the course of a woman’s life: forming a first union, leaving home, economic independence, and employment. It assesses their association with the probability of motherhood in Spain, a low-fertility country. The study focuses on the timing of these transitions and their particular conditions, as well as the order in which they occur. Data for the analysis are taken from the 2018 Fertility Survey (N = 7,819) conducted by the Spanish National Statistics Institute. We have applied event history models, specifically discrete-time logistic regression models. The study reveals varying relationships between life transitions and motherhood, emphasizing the relevance of both the order and specific characteristics of each transition. Forming a union is the main transition associated with motherhood, being moderated by the type of union, its stability, and by economic and employment circumstances. Leaving the parental home also shows a strong association with the likelihood of motherhood, although it also appears to be mediated by the woman’s economic, union, and employment status. Finally, access to employment favours motherhood, albeit to a lesser extent than the other life transitions.